The blue light receptor ZmFKF1a recruits ZmGI1 to the nucleus to accelerate shoot apex development and flowering in maize - Wu, Fengkai; Kang, Yan; Liu, Ling; Lei, Jingxin; He, Bing; He, Yafeng; Li, Jing; Liu, Fangyuan; Du, Qingguo; Zhang, Xuecai; Xu, Jie; Zhou, Zhanmei; et al. (Oxford University Press, 2025)
Photoperiod sensitivity poses a major obstacle to the expansion, breeding, and production of maize (Zea mays) in temperate regions. While the photoperiod-dependent FLOWERING LOCUS T (FT)/ZCNs pathway modulates floral development, the mechanism by which crops perceive specific light wavelengths and regulate flowering remains largely unknown. In this study, we demonstrate that the rhythmic expression of the blue light receptor FLAVIN-BINDING KELCH REPEAT F-BOX 1a (ZmFKF1a) is finely controlled by the Evening Complex (EC) components of LUX ARRHYTHMO 2 (ZmLUX2). ZmFKF1a interacts with GIGANTEA 1 (ZmGI1), stabilizing it and promoting its nuclear localization via a blue light-dependent mechanism. In the nucleus, ZmGI1 directly binds and activates Zea mays MADS-box 4 (ZMM4), a MADS-box gene specifically expressed in the shoot apical meristem, which drives floral transition. Genetic analyses revealed that ZmGI1 is epistatic to ZmFKF1a in promoting shoot apex development and accelerating flowering in maize. Our findings elucidate a ZmLUX2-ZmFKF1a–ZmGI1-ZMM4 regulatory module that fine-tunes photoperiodic flowering of day-neutral temperate maize lines, functioning independently of ZEA CENTRORADIALISs (ZCNs). Furthermore, transgenic maize overexpressing ZmFKF1a exhibited accelerated flowering and enhanced yield specifically in photoperiod-sensitive tropical maize lines under extreme natural long-day conditions, underscoring its potential application in improving maize production through precise manipulation of flowering traits. These insights advance our understanding of how blue light signaling orchestrates flowering time in maize and offer a promising strategy for optimizing crop performance in diverse environments.